Recent Nano-based Therapeutic Intervention of Bioactive Sesquiterpenes: Prospects in Cancer Therapeutics - Ansari, Mohammad A.; Badrealam, Khan F.; Alam, Asrar; Tufail, Saba; Khalique, Gulshan; Equbal, Mohammad J.; Alzohairy, Mohammad A.; Almatroudi, Ahmad; Alomary, Mohammad N.; Pottoo, Faheem H. (Current Pharmaceutical Design, 2020)
In the recent scenario, nanotechnology-based therapeutics intervention has gained tremendous impetus all across the globe. Nano-based pharmacological intervention of various bioactive compounds has been explored on an increasing scale. Sesquiterpenes are major constituents of essential oils (EOs) present in various plant species which possess intriguing therapeutic potentials. However, owing to their poor physicochemical properties; they have pharmacological limitations. Recent advances in nano-based therapeutic interventions offer various avenues to improve their therapeutic applicability. Reckoning with these, the present review collates various nano-based therapeutic intervention of sesquiterpenes with prospective potential against various debilitating diseases especially cancer. In our viewpoint, considering the burgeoning advancement in the field of nanomedicine; in the near future, the clinical applicability of these nano-formulated sesquiterpenes can be foreseen with great enthusiasm.
Keywords: nanoformulations